MANAGEMENT OF EROSIVE ORAL LICHEN PLANUS ASSOCIATED WITH CHRONIC HEPATITIS C - Medini, Taissir; Besbes, Amira; Nasri, Wafa; Ben Abdeljelil, Nouha L; Selmi, Jamil (Journal of Ayub Medical College Abbottabad, 2024)
Hepatic disorders are generally silent, with slow progress, and are usually detected when the organ's function is severely affected. Several studies have shown that oral lichen planus (OLP) is one of the most Hepatitis C-associated diseases. The emergence of such an extrahepatic manifestation is frequent and can lead to an early diagnosis. Patients with chronic hepatitis C virus (HCV) infection exhibit extensive forms of OLP, with frequent periods of exacerbation of symptoms refractory to treatment, which is commensurate with the severity of the liver disease. When treating OLP in HCV patients, researchers have diverged results. This case report presents an extensive, erosive OLP in an HCV-positive female patient for whom clinical management was tremendous. Full remission was obtained after topical corticosteroid application and several sessions of oral cavity sanitation. This clinical case demonstrates that dentists play a major role in OLP diagnosing, managing, and malignant transformation preventing. They may also contribute to the screening of hepatitis C infection.